Ethnobotanical knowledge, potential and geographical distribution of mortiño (Vaccinium floribundum Kunth) in the high Andean páramo, Colombia - Oliva Burbano, Johanna Nataly (2024)
Introduction. Mortiño (Vaccinium floribundum Kunth) faces significant genetic erosion due to anthropogenic pressure in the páramos, leading to the gradual loss of traditional knowledge about the plant. In Colombia, the lack of specific records has hindered the identification of associated species and the understanding of the distribution and living conditions of this plant. Objective. To develop a model of geographical and potential distribution of mortiño, quantify plant diversity, and analyze the associated species, along with the uses and significance of the species in its ecological context. Materials and methods. The study was conducted in El Encano, Nariño-Colombia, during the year 2021. A participatory action research methodology was implemented, involving surveys, interviews, field visits with the community, and participatory workshops. For the development of distribution maps, ArcGIS 10.5 and MaxEnt 3.4.4 software’s were used. Biological diversity indices, such as Shannon-Weiner and Simpson, along with the importance value, were determined to evaluate species richness. Results. The community emphasizes the use of mortiño in food and traditional medicine. Twenty-one associated species were identified, with the fern (Blechnum loxense Kunth) being the most important. The distribution of V. floribundum was linked to favorable climatic conditions, with temperatures ranging 8 and 16 °C and an altitudinal gradient between 2800 to 3200 meters above sea level. Conclusions. The study identified two suitable ecosystems for mortiño: the high Andean Forest and the páramo. The importance value index highlights the fern as the most representative species associated with mortiño, providing valuable information for the conservation and sustainable management of these ecosystems in the region.